DISABILITY FIQH FOR HUMAN SUSTAINABILITY AS MANIFESTING OF MADANI SOCIETY DEVELOPMENT - Fatmawati, Indah; Ma’arif, Darul; Dewi, Arlinta Prasetian (Jurnal 'Ulwan, 2025)
Regulations created in Indonesia often only favor people with disabilities and very few favor people with disabilities. This is due to the dominance of people with disabilities who are more in quantity than people with disabilities. However, the state must not neglect in providing guarantees of convenience to people with disabilities, especially in providing access to worship. This access is not only in the form of disability-friendly infrastructure, but also in the form of access to knowledge related to worship, such as the creation of disability-friendly fiqh rules that are religious rights. So far, there has been no fiqh that discusses disability, even the existing study of fiqh on disability is still in the form of an adhoc fatwa. The purpose of this study is to analyze how disability fiqh is a necessity for human sustainability, seen from the perspective of human rights and sharia maqashid as an effort to build a civil society. This research is a type of qualitative research (library research) using a conceptual approach. The data will be analyzed descriptively with the concept of KBB as part of human rights which is also in line with sharia maqashid. From this research, a common thread can be drawn that disability fiqh is very urgent to ensure the religious rights of people with disabilities as well as human rights guarantees and the purpose of sharia maqasid.